Characterization of the effect of Cr(VI) on humoral innate immunity using Drosophila melanogaster. Issue 11 (28th April 2014) - Pragya, P.; Shukla, A. K.; Murthy, R. C.; Abdin, M. Z.; Kar Chowdhuri, D.
ABSTRACT With the advancement of human race, different anthropogenic activities have heaped the environment with chemicals that can cause alteration in the immune system of exposed organism. As a first line of barrier, the evolutionary conserved innate immunity is crucial for the health of an organism. However, there is paucity of information regarding in vivo assessment of the effect of environmental chemicals on innate immunity. Therefore, we examined the effect of a widely used environmental chemical, Cr(VI), on humoral innate immune response using Drosophila melanogaster. The adverse effect of Cr(VI) on host humoral response was characterized by decreased gene expression of antimicrobial peptides (AMPs) in the exposed organism. Concurrently, a significantly decreased transcription of humoral pathway receptors (Toll and PGRP) and triglyceride level along with inhibition of antioxidant enzyme activities were observed in exposed organism. This in turn weakened the immune response of exposed organism that was manifested by their reduced resistance against bacterial infection. In addition, overexpression of the components of humoral immunity particularly Diptericin benefits Drosophila from Cr(VI)‐induced humoral immune‐suppressive effect. To our knowledge, this is the first report regarding negative impact of an environmental chemical on humoral innate immune response of Drosophila along with subsequent protection by AMPs, which may provide novel insight into host–chemical interactions. Also, our data validate the utility and sensitivity of Drosophila as a model that could be used for screening the possible risk of environmental chemicals on innate immunity with minimum ethical concern that can be further extrapolated to higher organisms. © 2014 Wiley Periodicals, Inc. Environ Toxicol 30: 1285–1296, 2015.